Blockade of glycosphingolipid synthesis inhibits cell cycle and spheroid growth of colon cancer cells in vitro and experimental colon cancer incidence in vivo - Jennemann, Richard; Volz, Martina; Bestvater, Felix; Schmidt, Claudia; Richter, Karsten; Kaden, Sylvia; Müthing, Johannes; Gröne, Hermann-Josef; Sandhoff, Roger (International journal of molecular sciences, 2021)
Colorectal cancer (CRC) is one of the most frequently diagnosed cancers in humans. At early stages CRC is treated by surgery and at advanced stages combined with chemotherapy. We examined here the potential effect of glucosylceramide synthase (GCS)-inhibition on CRC biology. GCS is the rate-limiting enzyme in the glycosphingolipid (GSL)-biosynthesis pathway and overexpressed in many human tumors. We suppressed GSL-biosynthesis using the GCS inhibitor Genz-123346 (Genz), NB-DNJ (Miglustat) or by genetic targeting of the GCS-encoding gene UDP-glucose-ceramide-glucosyltransferase- (UGCG). GCS-inhibition or GSL-depletion led to a marked arrest of the cell cycle in Lovo cells. UGCG silencing strongly also inhibited tumor spheroid growth in Lovo cells and moderately in HCT116 cells. MS/MS analysis demonstrated markedly elevated levels of sphingomyelin (SM) and phosphatidylcholine (PC) that occurred in a Genz-concentration dependent manner. Ultrastructural analysis of Genz-treated cells indicated multi-lamellar lipid storage in vesicular compartments. In mice, Genz lowered the incidence of experimentally induced colorectal tumors and in particular the growth of colorectal adenomas. These results highlight the potential for GCS-based inhibition in the treatment of CRC.